Монголын нүүрсний ордуудын органик петрологийн судалгааны үр дүнгээс - Л., Жаргал; Б., Эрдэнэцогт (Geological Issues, 2022)
This review includes the results of coal petrography. Maceral compositions are calculated on mineral matter free basis. Studied Mongolian coals are vitrinertite, duroclarite, clarodurite, and clarite. Vitirinte contents range from 38.8% to 96.6%, inertinte contents vary from 2.0% to 63.0%. Liptinite content is less than 13.7%.